Kontribusi Pendidikan Agama Kristen dalam Memperkokoh Iman Kristen di Tengah Pluralisme Agama - Lisa Sababalat; Joni Joni; Patrisius Liber; Semuel Linggi Topayung (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
Religious pluralism in Indonesia requires every religious community to live side by side with different beliefs. In the midst of this situation, Christian Religious Education (PAK) has a strategic role in strengthening the Christian faith, helping people to face the challenges of pluralism with strong understanding and belief. PAK not only teaches religious doctrine, but also shapes Christian character which includes love, forgiveness, truth and tolerance. Through inclusive learning methods, such as Bible study, interreligious dialogue, and character formation, PAK helps Christians understand their faith identity in depth and foster wise and loving attitudes towards followers of other religions. Therefore, PAK contributes to producing Christians who are firm in their beliefs, compassionate, and able to live in harmony in a religious society.